Genomic characterization and antifungal properties of Paenibacillus polymyxa YF, a promising biocontrol agent against Fusarium oxysporum pathogen of codonopsis root rot - Li, Ying; Su, Xu; Xi, Wenjie; Zheng, Yanli; Liu, Yang; Zheng, Wangshan; Wei, Shiyu; Leng, Yan; Tian, Yongqiang (Frontiers in Microbiology, 2025)
Root rot, a destructive soil-borne disease, poses a significant threat to a wide range of economically important crops. Codonopsis, a high-value medicine plant, is particularly susceptible to substantial production losses caused by Fusarium oxysporum-induced root rot. In this study, we identified a promising biocontrol agent for codonopsis root rot, Paenibacillus polymyxa YF. In vitro assay demonstrated that the strain YF exhibited a 70.69% inhibition rate against F. oxysporum and broad-spectrum antifungal activities against the selected six postharvest pathogens. Additionally, the strain YF demonstrated significant plant growth-promoting properties. Subsequent in vivo inoculation assays revealed that the strain YF effectively mitigated disease symptoms of F. oxysporum-induced root rot in codonopsis, even achieving a complete disease prevention efficacy rate of 100%. Our findings further elucidated that the robust biocontrol capacity of the strain YF against F. oxysporum is mediated through multiple mechanisms, including inhibition of fusaric acid secretion, downregulation of virulence-associated genes in F. oxysporum, and the production of multiple hydrolytic enzymes. Genomic analysis showed that the strain YF has a 5.62-Mb single circular chromosome with 5,138 protein-coding genes. Comprehensive genome mining of the strain YF also identified numerous genes and gene clusters involved in bio-fertilization, resistance inducers synthesis, plant colonization, biofilm formation, and antimicrobial activity. These findings provide insights into the biocontrol mechanisms of the strain YF and offer substantial potential for its further exploration and application in crop production.